Cultural differences in decision making - Weber, Elke (Henry Stewart Talks, 2011)
What is culture?, What is decision making?, How does culture influence decisions?, How do cultures differ?, How to interpret cultural differences?, Person vs. situation, Current situation vs. longstanding cultural differences
Reviewed at 2018/03/29